Epidemiology of Paediatric Fractures at Koshi Hospital, A Tertiary Center in Eastern Nepal - Yadav, Ram Kumar; Yadav, Safal (Birat Journal of Health Sciences, 2024)
Introduction: Paediatric trauma is a leading cause of disability, hospitalization and may lead to mortality in pediatric population. Incidence and nature of fracture varies according to region, culture, seasonal variations and age. Children are more prone to have injury at play grounds, due to fall from height and also due to road traffic accident due to unmanaged traffic and lack of road safety measures. Identification of specific high-risk injury patterns may lead to improved care and outcome. This study aims to find out the epidemiological profile of paediatric injuries presenting to a tertiary care hospital in eastern Nepal. Objective: To study the common fractures and their management in the paediatric age group at Koshi hospital. Methodology: This was a hospital based retrospective cross-sectional study done among 424 paediatric patients at Koshi hospital from January 2021 to December 2021.Ethical clearance was taken from Nepal health research council . Data collection was done from the outpatient (OPD), emergency and the operation room records and was compiled in Microsoft excel 2007. Results: A total of 424 paediatric fractures were taken into study over the duration of one year. Out of which 288 were male (67.92%) and 136(32.08%) were female. Playground injuries were the most common cause of paediatric fractures (49.76%) followed by fall from height (27.35%) and road traffic accident (12.26%). Distal radius and ulna fracture was found to be most common (30.89%). Conclusion: Distal radius and ulna is the commonly fractured bone followed by supracondylar fractures of the humerus. Most of the paediatric fractures can be managed conservatively. Supervised play in the grounds, at home and at schools are important because paediatric injuries most of the times can be prevented to decrease the morbidity and mortality in the paediatric population. Proper knowledge and awareness of the traffic rules and zebra crossings should be implemented with local community participation and cooperation.